Profile of fungal blood stream infection (BSI) in neonate at tertiary care hospital in South India - C., Shanmuga Sundaram; C. N., Kamalarathnam (International Journal of Contemporary Pediatrics, 2018)
Background: Advancement in neonatal care has led to remarkable improvement in survival of new-born. Fungal infections in new born are an important health problem associated with substantial morbidity and mortality. The objective of this study was to assess the prevalence and epidemiology of neonatal fungal blood stream infection and to analyze risk factor associated with mortality due to fungal septicemia. Methods: This is a retrospective study of all neonatal fungal cases admitted from July 2016 to June 2017 to a tertiary care hospital in South India. Results: Isolation rate of fungal blood stream infection was 3.3%. Risk factors observed for candida blood stream infection were Broad spectrum antibiotic usage >7 days (91.18%) followed by central line >7 days (58.9%) and total parenteral nutrition (50.68%). Poor weight gain (71.23%), respiratory distress (68.4%) are common clinical presentation. Mortality among candida blood stream infection was 29 (39.72%). On step-wise logistic regression analysis, prolonged rupture of membrane and endotracheal tube placement for more than 7 days were significant independent predictors of mortality in neonatal candida blood stream infection. Conclusions: Candida blood stream infection is significant problem in our unit. It occurs in 3.3 %of neonates admitted in our unit and accounts for 34% of blood culture positive sepsis. Non-albican candidiasis is the predominant agent causing candida blood stream infection. Fungal prophylaxis may be recommended in neonates with risk factors like birth weight less than 1500 gms, those requiring ventilation for more than 7 days, those on total parenteral nutrition for more than 7 days and those on prolonged broad-spectrum antibiotics. It reemphasizes the need for aseptic insertion, maintenance, early identification of catheter related infection and early removal of central line.